Multiple resistive switching behaviours of CH3NH3PbI3 perovskite film with different metal electrodes - How, Gregory Thien Soon; Talik, Noor Azrina; Yap, Boon Kar; Nakajima, Hideki; Tunmee, Sarayut; Goh, Boon Tong (Elsevier, 2019)
The utilization of defects in organic-inorganic hybrid perovskite materials such as CH3NH3PbI3 is beneficial for memory applications. In this work, a simple CH3NH3PbI3 memory device with various commonly used electrodes such as aluminium (Al), silver (Ag), and gold (Au) yielded different switching behaviours. Using Al in ITO/CH3NH3PbI3/Al device reveals Resistive Random Access Memory (ReRAM) behaviour with a SET voltage of 4.5 V and can be RESET by applying a negative sweep voltage above 1.3 V due to the formation of iodide vacancy filament. Interestingly, by using Ag and Au cathodes to replace Al, yielded Write-Once-Read-Many (WORM) resistive switching characteristics. The conversion process from OFF to ON occur at around 4.7 V and 4.0 V for Ag and Au, respectively. The “shorting effect” remains even though a reverse voltage was applied indicating data retention. These fabricated devices could contribute to further understanding of selecting the right electrodes and open up new possibility of studies in the direction of resistive switching memory applications.